DIVERSITY OF POLYCHAETES OF A BRAZILIAN TROPICAL ISLAND (MORRO DE SÃO PAULO, BAHIA): A PRELIMINARY STUDY - Costa, Dimítri de Araújo; Prata, Jéssica; Lima, Silvio Felipe Barbosa; Christoffersen, Martin Lindsey (Revista Nordestina de Zoologia, 2023)
Polychaetes (Annelida) are typical marine invertebrates associated with macroalgae and coral reef environments, with a particular emphasis on tropical waters. In this study, 44 specimens were collected, belonging to ten families, 13 genera and 13 species, which the families Nereididae (with three species) and Amphinomidae (two species) were the most representative. The species Terebella plagiostoma (with 10 individuals), Ceratonereis singularis (nine) and Eurythoe complanata (nine) were the most abundant. This work represents the first study of polychaetes performed at the Morro de São Paulo region (Tinharé Island), a protected island from Northeast Brazil (state of Bahia). The samples (algae in the fringing reef ecosystems) were collected in 2015, at low tide in the intertidal to shallow subtidal zones. The species Hyboscolex longiseta is reported here for the first time in the Atlantic Ocean of South America. Errant polychaetes predominated at the collected samples (61.36% of the total abundance). These numbers evidence how little we know about coastal marine invertebrate fauna in Brazil and indicate the need for further sampling, especially on protected islands.